Identification of freshwater microbiota and physicochemical analysis of water Waduk Lhok Batee Jeumpa - Dani Pratama Putra; Ernawita Ernawita; Yayuk Kurnia Risna (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2023)
Biota components can provide an overview of the physical, chemical and biological conditions of a waters. One biota that can be used as a biological parameter in determining the condition of a waters is biota. Changes in the quality of water and its living substrate greatly affect the abundance and diversity of biota. The aim of this study was to identify fresh water microbiota and physicochemical analysis of water in the Lhok Batee Jeumpa Reservoir. The research method used is a combination of qualitative and quantitative research. Based on the research results, there are 13 types of Plankton consisting of 12 families in the Lhok Batee Reservoir. Plankton diversity is included in the low category with a diversity index of 0.4296. Dissolved Oxygen (DO) levels obtained the lowest value in sample 2-A of 4.70 mg/L and the highest value in samples 1-B, 4-B and 5-A of 5.20 mg/L, according to the standard quality Class 2 (4 mg/L). Biochemical Oxygen Demand (BOD) levels obtained the lowest value in sample 5-A of 1.00 mg/L and the highest value in sample 3-A of 12.50 mg/L, in accordance with Class 2 quality standards (3 mg/ L). Chemical Oxygen Demand (COD) levels obtained the lowest value in sample 1-B of 20.22 mg/L and the highest value in sample 5-B of 84.76 mg/L, according to Class 2 quality standards (25 mg/L).